Failure of a Solar Filament Eruption Caused by Magnetic Reconnection with Overlying Coronal Loops - Leping Li; Hongqiang Song; Yijun Hou; Guiping Zhou; Baolin Tan; Kaifan Ji; Yongyuan Xiang; Zhenyong Hou; Yang Guo; Ye Qiu; Yingna Su; Haisheng Ji; et al. (The Astrophysical Journal)
The failure of a filament eruption caused by magnetic reconnection between the erupting filament and the overlying magnetic field has been previously proposed in numerical simulations. It is, however, rarely observed. In this study, we report a reconnection between an erupting filament and its overlying coronal loops that results in the failure of the filament eruption. On 2023 September 24, a filament was located in active region 13445. It slowly rose, quickly erupted, rapidly decelerated, then finally stopped, with an untwisting motion. As a failed eruption, the event is associated with an M4.4 flare but no coronal mass ejection. During the eruption, the filament became bright, and the overlying loops appeared first in the high-temperature channels. They have average temperatures of ∼12.8 and ∼9.6 MK, respectively, indicating that both of them were heated. Two sets of new loops, separately connecting the filament endpoints and the overlying loop footpoints, then formed. Subsequently, the heated overlying loops were seen sequentially in the low-temperature channels, showing the cooling process, which is also supported by the light curves. Plasmoids formed and propagated bidirectionally along the filament and the overlying loops, indicating the presence of plasmoid instability. These results suggest that reconnection occurs between the erupting filament and the overlying loops. The erupting filament eventually disappeared, with the appearance of more newly formed loops. We propose that the reconnection between the erupting filament and the overlying loops ruins the filament completely, hence resulting in the failed eruption.